2018
DOI: 10.1101/340257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of susceptible and resistant potato cultivars on bacterial communities in the tuberosphere of potato in soil suppressive or conducive to common scab disease

Abstract: Connections between the structure of bacterial communities in suppressive soils and potato resistance to common scab (CS) are not well understood. In this study, one resistant and one susceptible cultivar were grown in a conducive and suppressive field to assess cultivar resistance × soil suppressiveness interactions. The resistant cultivar had a higher Mg content in periderm compare to susceptible cultivar, while suppressive soil had lower pH (5.3 vs 5.9), N, C, P, Ca contents but higher Fe and S compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
0
0
1
Order By: Relevance
“…PC1 and PC3 were considered the key factors causing the difference in fungal communities between ZM20 and resistant varieties (Figure 3(b)). Kopecky et al found that both resistant and sensitive species had the differences on the diversity, structure, and composition of soil bacterial communities [32][33][34]. Differences in rhizosphere soil microorganisms of different wheat cultivars may be caused by different plant genotypes, which may affect the composition and abundance of annual plant microbial communities.…”
Section: The Microbial Community Structure Of the Highlymentioning
confidence: 99%
“…PC1 and PC3 were considered the key factors causing the difference in fungal communities between ZM20 and resistant varieties (Figure 3(b)). Kopecky et al found that both resistant and sensitive species had the differences on the diversity, structure, and composition of soil bacterial communities [32][33][34]. Differences in rhizosphere soil microorganisms of different wheat cultivars may be caused by different plant genotypes, which may affect the composition and abundance of annual plant microbial communities.…”
Section: The Microbial Community Structure Of the Highlymentioning
confidence: 99%
“…Observou-se, em experimentos em casa de vegetação utilizando duas linhagens de Streptomyces não patogênicas contra uma linhagem de S. turgidiscabies, uma total inibição do aparecimento de lesões nos tubérculos (HILTUNEM & KOLLONIEMI 2017). Aplicações repetidas em campo da linhagem de Streptomyces 272 não patogênica resultaram na supressão de sintomas da sarna no decorrer dos anos (KOPECKY et al 2018). Testes empregando diferentes combinações de antagonistas do gênero de Streptomyces em conjunto com ureia resultaram na inibição do patógeno quando comparados com ensaios realizados somente com o antagonista (OT- .…”
Section: G) Controle Químicounclassified